Rate Constants and Rheological Properties of the Ultrasonic Degradation of Carboxymethyl Cellulose - Abuissa, Hitham M. (Scientific Journal for Faculty of Science-Sirte University, 2021)
To degrade the polysaccharide with high molecular weight the effectiveness of ultrasound for carboxymethyl cellulose (CMC) in aqueous solution has been studied at a time of 60 min and temperature of 25 ̊C and for polymer solution with concentration up 0.1 g/L. The Huggins equation was appropriate to apply to the intrinsic viscosity of CMC before sonication to understand the influence of salt on degradation, CMC solution was premixed with 0.1 M NaCl, before ultrasonication. Developed a kinetic model, successfully implement to predict and quantify rates of degradation and efficiency. The values of reaction rate constants and reaction orders were found related to the salt and the concentration used, suggesting that, the presence and absence of salts could increase or decrease the degradation by ultrasonic radiation through adjusting the molecular conformation of CMC